Effect of Toxoplasmosis on hematological, biochemical and immunological parameters in pregnant women in Tikrit city, Iraq - Omaima I. Mahmood (Tikrit Journal of Pure Science)
The aim of the present study was to detect the effect of infection with Toxoplasma gondii on hematological, biochemical and immunological parameters in pregnant women. Blood samples, 101 in the total number, were subject to serological test (ELISA test) collected between first of September 2013 to the end of March 2014 from pregnant women: 76 seroposative toxoplasmosis and (25) seronegative toxoplasmosis (control group) divided into two groups according to their ages (16-26 years and 27-46 years). Hematological parameters in whole blood samples were examined. Liver enzyme activity such as Alanine aminotransferase (ALT), Aspartate aminotransferase (AST) and Alkaline Phosphatase (ALP) also urea and creatinine concentration in serum were determined. Besides, the levels of interleukins (IL-6 and IL-10) were analyzed. In infected groups WBCs counts, ALT, AST, ALP activities, urea and creatinine concentration, IL-6 and IL-10 levels were increased significantly p≤0.05, while the Hb and PCV levels decreased significantly p≤0.05 when compared to control groups